Consciousness of some environmental problems among Warszaw youth - Siniarska, Anna; Wysokińska, Katarzyna (Studia Ecologiae et Bioethicae, 2005)
This paper concerns the present and most important environmental problems related to the state of environment and economic development on the local, national and world scale. The material consists of 414 pupils from the last grade of high schools: 108 boys and 88 girls from the two schools with higher level of education (HEL) and 106 boys and 112 girls from two schools with lower level of education (LEL). The George H. Gallup Institute inquiry was used and pupils answered on 13 questions. The survey was conducted from October to November 2003. Pupils were surveyed via face to face interviews. Answers were considered regarding the level of education and gender of responders, as well as it was compared with results of the 1992 Gallup Institute survey from 22 nations covering most continents and all levels of economic development. In each country, representative samples of adults (generally 1000 or more) were investigated. The Warsaw youth better estimates the quality of their local environment (Warsaw) than nation’s and world’s one. So do the majority of respondents from 22 countries. The most important environmental problem facing Poland, according to Warsaw pupils, is general pollution, whereas the majority of respondents from 22 countries are more likely to volunteer air and water pollution. The answer for the question “which one – the government, business and industry or citizens have the primary responsibility for protecting the environment?” is different comparing the Warsaw youth and respondents from 22 nations. The first one points to citizens, whereas the majority of respondents from most nations assign primary responsibility for environmental protection to the government. Majority of respondents in Warsaw and in 22 nations state that environmental protection should have priority even at the risk of slowing down economic growth. Responders from Warsaw, Asia, East and West Europe and Scandinavia charge local environmental problems like poor water and air quality as very serious. The cause of nation’s environmental problem the high school pupils see in waste by individuals, however across the 22 nations responders are most likely to point to business and industry as the major contributors of these problems. According to actions the government could take to help solve environmental problems the Warsaw youth and majority of the Gallup survey responders point to stronger environmental protection laws for business and industry. The only responders of nations with high income ban the sale of products that are unsafe for the environment. Over half of the Warsaw youth and most responders from high income nations indicate a willingness to pay higher prices for increased environmental protection. Majority of the high school pupils and responders of 22 nations are more likely to see citizen actions as being effective for environmental protection (answers: great deal, fair amount). The personal involvement in adding the environment is base on avoiding environmentally harmful products - such declaration give most of responders from Warsaw, as well as from 22 nations. The the Warsaw youth and majority of responders from the Gallup survey point to loss of rain forest as the global problem. Majority of responders both from Warsaw and 22 nations say that they either “strongly favor” or “somewhat favor” their own government “contributing money to an international agency to work on solving global environmental problems.” The problem of responsibility for world’s environmental problem is seen a little different by nations according to their economic level. The responders of low and middle income ations, including the Warsaw youth, blame both, industrialized and developing nations for this problem, whereas high income responders are most likely to blame developed nations only. The comparison according to gender and levels of education reveled that girls act more determinedly and with larger commitment in answering the questions concerning current environmental problems, and this is more express in the school with HEL than LEL. The reverse situation is seen in boys where those more active attend the LEL schools. The important conclusion concerns the open-ended question: “Thinking about our nation as a whole, what is the most important environmental problem facing our nation?” There were much more responders from the LEL schools saying “I do not know” (25% of boys and 30% of girls) than from the HEL schools (11% and 15%, respectively). This shows how important is to include the environmental education to the school educational program in the whole country.